ABC transporters affects tumor immune microenvironment to regulate cancer immunotherapy and multidrug resistance. (January 2023) - Fan, Jingyi; To, Kenneth Kin Wah; Chen, Zhe-Sheng; Fu, Liwu
Abstract: Multidrug resistance (MDR) is the phenomenon in which cancer cells simultaneously develop resistance to a broad spectrum of structurally and mechanistically unrelated drugs. MDR severely hinders the effective treatment of cancer and is the major cause of chemotherapy failure. ATP-binding cassette (ABC) transporters are extensively expressed in various body tissues, and actively transport endogenous and exogenous substrates through biological membranes. Overexpression of ABC transporters is frequently observed in MDR cancer cells, which promotes efflux of chemotherapeutic drugs and reduces their intracellular accumulation. Increasing evidence suggests that ABC transporters regulate tumor immune microenvironment (TIME) by transporting various cytokines, thus controlling anti-tumor immunity and sensitivity to anticancer drugs. On the other hand, the expression of various ABC transporters is regulated by cytokines and other immune signaling molecules. Targeted inhibition of ABC transporter expression or function can enhance the efficacy of immune checkpoint inhibitors by promoting anticancer immune microenvironment. This review provides an update on the recent research progress in this field.